Bioproduction of Natural Phenethyl Acetate, Phenylacetic Acid, Ethyl Phenylacetate, and Phenethyl Phenylacetate from Renewable Feedstock. Issue 9 (10th February 2022) - Sekar, Balaji Sundara; Li, Xirui; Li, Zhi
Abstract: Natural phenethyl acetate (PEA), phenylacetic acid (PAA), ethyl phenylacetate (Et‐PA), and phenethyl phenylacetate (PE‐PA) are highly desirable aroma chemicals, but with limited availability and high price. Here, green, sustainable, and efficient bioproduction of these chemicals as natural products from renewable feedstocks was developed. PEA and PAA were synthesized from l ‐phenylalanine (l ‐Phe) via novel six‐ and five‐enzyme cascades, respectively. Whole‐cell‐based cascade biotransformation of 100 mm l ‐Phe in a two‐phase system (aqueous/organic: 1 : 0.5  v / v ) containing ethyl oleate or biodiesel as green solvent gave 13.6 g L −1 PEA (83.1 % conv.) and 11.6 g L −1 PAA (87.1 % conv.), respectively. Coupled fermentation and biotransformation approach produced 10.4 g L −1 PEA and 9.2 g L −1 PAA from glucose or glycerol, respectively. The biosynthesized PAA was converted to natural Et‐PA and PE‐PA by esterification using lipases with ethanol or 2‐phenylethanol derived from sugar, affording 2.7 g L −1 Et‐PA (83.1 % conv.) and 4.6 g L −1 PE‐PA (96.3 % conv.), respectively. Abstract : Smells like sustainability : Sustainable and high‐yielding bioproduction of phenethyl acetate, phenylacetic acid, ethyl phenylacetate, and phenylethyl phenylacetate as high‐value natural aroma chemicals are achieved from renewable feedstock l ‐phenylalanine with novel artificial enzyme cascades, or from glucose and glycerol with combined artificial enzyme cascades and natural pathway.